Полупроводниковый генератор миллиметрового диапазона на запредельном волноводе - Plaksin, S. V.; Pogorelaja, L. M.; Sokolovskij, I. I.; Lukash, V. S.; Sokolovskij, I. I. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The results of optimizing the designs of semiconductor generator diodes based on the electron intervalley transfer effect (MIT diodes) and the oscillatory circuits of self‑oscillators using the specific properties of wave‑guiding electrodynamic structures are presented. This optimization makes it possible to improve the performance characteristics of electromagnetic radiation sources in the millimeter wavelength band.